NUMERICAL SIMULATION OF AIRFOILS APPLIED TO UAVs - P. Corrêa, P. C.; Barcelos, M. N. D. (Revista de Engenharia Térmica, 2014)
This essay aims the process optimization when referred to aeronautical projects. By using mesh generators softwares and simulations made in CFD, the article employs numerical techniques to simulate airfoils and shows that is possible to extract accurated and conservative outcomes when compared to wind tunnel results. The test cases studied were based on the Selig 1223 type of airfoil and developed into the ANSYS platform, whereas by using the ICEM mesh tool, structured meshs were generated and imported to the CFX enviroment, where they could be simulated and analyzed.